Rhu Keystroke Touchscreen Benchmark - Mohamad El-Abed; Mostafa Dafer; Christophe Rosenberger (2018 International Conference on Cyberworlds (CW), 2018)
Introduction In recent years, PANLAR has addressed gender equity. Objectives To analyze the characteristics of speakers participating in PANLAR congresses and to compare the distribution of speakers by gender. Methods Speakers who participated in the annual PANLAR congresses from 2021 to 2024 were identified by reviewing the corresponding scientific programs. The following data were recorded: age, sex, nationality, country of residence, speaker category, type of participation (moderator, speaker at general conferences, or speaker at industry-sponsored symposia), years in the specialty, and workplace. Statistical analyses included descriptive statistics, the χ2 or Fisher exact test, and the Student t test. Results A total of 430 speakers participated in the four annual PANLAR congresses held from 2021 to 2024. The median age was 48 years (IQR: 40 to 60), and 231 speakers (53.7%) were men. Of these, 337 were adult rheumatologists (79.3%). The main countries of origin of the speakers were Colombia (21.6%), Brazil (20.9%), and Argentina (13.7%). Among the speakers, 114 participated as moderators, 337 as speakers at general conferences, and 67 as speakers at pharmaceutical industry-sponsored symposia. Among rheumatologists who treated adult patients, the proportion of men was higher than that of women in both moderator roles and general conferences, although these differences were not statistically significant (men 58.4% vs. women 41.2%, and men 53.6% vs. women 46.4%, respectively; p=NS). Men participated significantly more often than women in pharmaceutical industry-sponsored symposia (men 71.4% vs. women 28.6%; p=0.005). The mean numbers of moderator roles, general lectures, and industry-sponsored symposia were also significantly higher among men than among women. Conclusion Men accounted for a higher proportion of moderators and speakers at PANLAR annual meetings during the study period, with a more pronounced gender disparity in pharmaceutical industry-sponsored symposia.